Estrategias para la enseñanza de lecto-comprensión de textos jurídicos en inglés en la carrera de Abogacía - Curto, Jorge Christian (2017)
The aim of this essay is to reflect about the foreign language as a subject in the Law degree course. What kind of difficulties do students face when they have to read a legal text written in English? What pedagogic strategies may teachers use to help them overcome such difficulties? What tools may students use? This essay tries to answer those questions. The concept of reading comprehension, certain characteristics of the legal jargon, students' needs and teaching methodology are some of the aspects considered.